Efficient derivation of chimeric-antigen receptor-modified TSCM cells - Kranz, Emiko; Kuhlmann, Charles J.; Chan, Joshua; Kim, Patrick Y.; Chen, Irvin S. Y.; Kamata, Masakazu (Frontiers in Immunology, 2022)
Chimeric-antigen receptor (CAR) T-cell immunotherapy employs autologous-T cells modified with an antigen-specific CAR. Current CAR-T manufacturing processes tend to yield products dominated by effector T cells and relatively small proportions of long-lived memory T cells. Those few cells are a so-called stem cell memory T (TSCM) subset, which express naïve T-cell markers and are capable of self-renewal and oligopotent differentiation into effector phenotypes. Increasing the proportion of this subset may lead to more effective therapies by improving CAR-T persistence; however, there is currently no standardized protocol for the effective generation of CAR-TSCM cells. Here we present a simplified protocol enabling efficient derivation of gene-modified TSCM cells: Stimulation of naïve CD8+ T cells with only soluble anti-CD3 antibody and culture with IL-7 and IL-15 was sufficient for derivation of CD8+ T cells harboring TSCM phenotypes and oligopotent capabilities. These in-vitro expanded TSCM cells were engineered with CARs targeting the HIV-1 envelope protein as well as the CD19 molecule and demonstrated effector activity both in vitro and in a xenograft mouse model. This simple protocol for the derivation of CAR-TSCM cells may facilitate improved adoptive immunotherapy.